Evaluation of NEMO-based approaches for route optimization - Mosa, Ahmed A.; Hassan Abdalla Hashim, Aisha; Saeed, Rashid Abdelhaleem; Khalifa, Othman Omran (2011)
The development of mobile IPv6 protocol marked the first attempt to support mobility of individual devices (hosts) such as laptops, mobile phones and PDAs. However, the recent trend is a drive to support mobility of the entire network (Network Mobility - NEMO). NEMO provides mobility solution based on Mobile Router (MR) concept. The mobile routers maintain session continuity between the Mobile Network Nodes (MNNs) and their Corresponding Nodes (CNs) irrespective of the MR's change of point of attachment. Specifically with NEMO Basic Support protocol, all data packet to or from MNNs must go through the (MR-HA) via bidirectional tunnel (BDT). Thus, the Home Agent (HA) is a critical element for communications between MMNs and its CNs. However, BDT generates sub-optimal and inefficient routing path thereby, increasing the path length and delay. Furthermore, multiple MRs can be connected together (two NEMOs or more) to form nested NEMO, but the network performance suffers the Pinball routing problems, due to different levels of IP encapsulations. Therefore, this paper aims to describe the issues of the Route Optimization (RO). Furthermore, it presents highlights of different scenarios of NEMO RO and analysis of the corresponding proposed solutions.